A REVIEW ON ROLE OF AYURVEDA IN THE MANAGEMENT OF STRESS - Sharma, Richa (International Journal of Ayurveda and Pharma Research, 2018)
In the present era, life is full of desires, demands, workloads, deadlines, frustrations, irritations, squabbles etc. which lead into production of stress. Stress may be physical, physiological or psychological. Out of these stresses, psychological stress require specific concern as it may be dangerous to someones physical & mental health, personal safety or well being. Incompatibility with others, marital discord, quarrel, torture, abuse, self doubt are various situations related with emotions, anxieties, interpersonal, social or behavioural events and thus producing psychic stress. Small amount of stress is useful as it helps us to perform better under pressure, motivate us to do our best. But beyond a certain limit stress start causing severe destruction to health, mood, productivity, relationship & quality of life. Ayurveda is a science and art of appropriate living which helps us to achieve longevity with a better quality. It has proven to be definitely effective in the management of stress related problems of life caused by several reasons. It includes knowledge of complete balance of body, mind and spirit including emotions and psychology on all levels. It treat stress by various life style modifications e.g. Dincharya, Sadvrit etc. and by use of Medhyadravya, Satvavajaychikitsa, Panchkarma, Shirodhara etc. Ayurvedic methods of treating stress not only maintain the balance in body & mind but also progressively raise the level of inner happiness & satisfaction. This paper focuses review on role of Ayurveda in the management of stress.